Existentials and Locatives in Romance Dialects of Italy - Bentley, Delia (Oxford University Press, 2015)
This volume provides the first ever large-scale comparative treatment of there sentences (there copula NP), reporting the results of a survey of Italo-Romance and Sardinian dialects of Italy. The volume comprises detailed discussions of focus structure, predication and argument realization, the definiteness effects, and the linking from semantics to syntax in there sentences, advancing novel proposals in each case. The testing of influential hypotheses on existential constructions against first-hand dialect evidence leads the book to argue that existential and locative there sentences differ in focus structure and semantics, although their not being predicate focus constructions and the non-canonicality of the predicate-which is typically referential-is reflected in their shared morphosyntactic features. The hypothesis that the pivot is the predicate of the existential construction is adopted in the analysis, although a distinction is drawn between referential and non-referential pivots, which explains variation in pivot behaviour in morphosyntax. The volume also provides the historical background of Romance there sentences, relying on the findings of the analysis of a substantial corpus of early Italo-Romance vernacular texts.